Understanding the metacognition and impulsivity issues with clinical and cognitive insight in borderline personality disorder – A cross sectional study - Rajnish Raj; Aaliya Khanam; Zaid A. Wani; Afifa Afreen; Simranjeet Kour; Ajaz A. Khan; Inaamul Haq (Industrial Psychiatry Journal)
Background: Borderline personality disorder (BLPD) is one of the most common personalities disorders frequently encountered in the outpatient setup. Aim: Understanding the role of impulsivity and metacognition in clinical and cognitive insight among BLPD patients. Materials and Methods: A cross-sectional study was performed among 81 patients diagnosed with BLPD. Sociodemographic details were collected, and the Borderline Personality Questionnaire (BPQ), Beck Cognitive Insight Scale (BCIS), Metacognitive Questionnaire (MCQ-30), Urgency premeditation perseverance sensation seeking – impulsive behavior scale – short version (UPPS-S), and Scale to assess unawareness of mental disorder (SUMD) were applied to assess severity symptomatology, cognitive insight, metacognition, impulsivity and clinical insight, respectively. Results: The mean age ± SD of subject was 22.19 ± 3.79, with a female preponderance (N = 61, 75.3%). The mean ± SD of BCIS, MCQ-30, UPPS-S, SUMD, and BPQ was 7.78 ± 4.11, 66.96 ± 14.95, 50.98 ± 11.72, 5.53 ± 2.36, and 57.56 ± 9.00, respectively. The cognitive (BCIS) and clinical insight (SUMD) were significantly correlated (r = −0.26, P = 0.01). The impulsivity (UPPS) was also positively correlated with BPQ, (r = 0.26, P = 0.01). In regression analysis, a significant negative relation was observed with MCQ-30 (Cognitive self-consciousness) (β = −0.341, 95% CI = −1.022 to − 0.186, P = 0.005) when predicting BPQ. A significant negative relation of Negative urgency with BCIS (β = −0.339, 95% CI = −0.703 to − 0.054, P = 0.023) and a positive relation with SUMD (β =0.331, 95% CI = 0.032 to 0.392, P = 0.022) were obtained. Conclusion: The results of this study can be used in clinical practice by strengthening existing therapies aiming at these areas and thereby enhancing therapeutic alliance, adherence, and prognosis.